Family Functioning Mediates the Relationship Between Activities of Daily Living and Poststroke Depression. Issue 1 (January 2021) - Yang, Li; Zhao, Qiuli; Liu, Hongli; Zhu, Xuemei; Wang, Kunxiao; Man, Jing
Abstract : Background: Poststroke depression is common and includes depressive and somatic symptoms. However, few studies have confirmed the influence of family functioning on poststroke depression or explored the association among daily activities, family functioning, and poststroke depression. Objectives: We examined the independent risk factors of daily activities and family functioning for poststroke depression and identified the mediating effect of family functioning on the association between daily activities and poststroke depression. Methods: This cross-sectional study design used convenience sampling to recruit 422 stroke survivors from the neurology department of a hospital in Harbin, China, from February to July 2018. We assessed participants' demographic and clinical variables, including depression, daily activities, and family functioning. Pearson's correlations and multiple linear regression analyses were conducted, and a path analysis with bootstrapping was utilized to define direct/indirect effects. Results: Daily activities and family functioning had a significant and direct negative effect on participants' depression. The indirect effect of 1, 000 bootstrap samples after bias correction with a 95% confidence interval was below zero, indicating that family function had a significant mediating effect on the association between depression and daily activities. Discussion: This study revealed the importance of family functioning in the association between depression and daily activities in stroke survivors. To the best of our knowledge, this study was the first to explore the mediating role of family functioning in poststroke depression, emphasizing the importance of family for the mental health of stroke patients. To reduce the incidence of poststroke depression, interventions that enhance daily activities and family functioning may include nurses, family therapists, rehabilitation physicians, and community workers.